Prevalence of overweight and obesity in 10-year-old schoolchildren in a municipality in southern Brazil (Research, Society and Development, 2021)
Objective: To estimate the prevalence of overweight and obesity in 10-year-old schoolchildren in a city in southern Brazil and to explore possible association with sex and type of school. Methods: A cross-sectional study nested in a cohort study was carried out. 942 schoolchildren, aged 10 years enrolled in public and private schools, from families residing in Palhoça, SC, Brazil, were included. Weight and height were collected. The body mass index was calculated using Z score. The chi-square test was used to analyse the association between the studied variables. Results: The prevalence rate of overweight was 39.5%, 22.8% being overweight, 14.3% obesity and 2.4% severe obesity. The prevalence rates of obesity and severe obesity were statistically higher in males. Conclusion: The prevalence rates of overweight and obesity in the studied population were high, being higher among male students.